U-shaped relationship between the triglyceride glucose index and the risk of incident diabetes among MASLD adults: a retrospective cohort study - Cao, Changchun; Zhang, Xiaohua; Han, Yong; Hu, Haofei; Wang, Yulong (Frontiers in Endocrinology, 2025)
BackgroundPrevious research has indicated that the triglyceride glucose index (TyG-i) may serve as a potential risk factor for type 2 diabetes (T2D). However, there is a paucity of studies addressing the relationship between TyG-i and T2D, specifically in patients with metabolic dysfunction-associated steatotic liver disease (MASLD). Consequently, this longitudinal study aims to investigate the association between TyG-i and the onset of T2D in a cohort of Japanese adults with MASLD.MethodsThis retrospective cohort study included a total of 2,507 subjects diagnosed with MASLD. To evaluate the association between the TyG-i and the risk of developing T2D, Cox proportional hazards regression models were employed to estimate hazard ratios (HR) along with 95% confidence intervals (CI). Additionally, nonlinear associations between them were investigated utilizing restricted cubic spline models.ResultsDuring a mean follow-up period of 6.00 years, a total of 204 adults with MASLD developed T2D. After adjusting for potential confounding factors, elevated TyG-i was found to be independently associated with an increased risk of developing T2D (HR: 1.48, 95% CI: 1.05-2.09, P = 0.0256). Additionally, a U-shaped relationship between the TyG-i and the incidence of T2D was identified. A significant negative association was observed between TyG-i and T2D risk when TyG-i levels were below 7.94 (HR: 0.21, 95%CI: 0.07-0.66, P = 0.0072). Conversely, TyG-i values exceeding the threshold were positively correlated with T2D risk (HR: 1.76, 95% CI: 1.23-2.52, P = 0.0020).ConclusionA U-shaped association was identified between baseline TyG-i and the incidence of T2D in a Japanese population with MASLD. This inflection point in TyG-i serves as a valuable clinical indicator to differentiate individuals at lower versus higher risk of developing T2D. These findings indicate that maintaining TyG-i near the inflection point may be beneficial in reducing the risk of developing diabetes in patients with MASLD.